Kerusakan Total Menurut Calvinisme Dan Implikasinya Bagi Jemaat GMIM Bukit Moria Tondei Satu Wilayah Motoling Lolombulan - Lumowa, Fangry Franclien (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2022)
The Understanding of biblical doctrine is very important thing for Christianity. Proper understanding affects to the practice of life and faith of church people. The Total depravity doctrine by calvinisme is based on biblical hermeneutic. This doctrine explains about the condititon of all humans who are full of sin and need Jesus Christ as The Only savior.There are several objectives of this research, namely, to analyze the understanding of church people about total depravity doctrine, to analyze the understanding of church people about atonement of sins by Jesus Christs, to analyze the diffrence of opinion of church people and Calvinism. The Research method used is qualitative methode. Data colletion techniques used are observation, interview, litarature study and discussion the research result.From the results of the research found in GMIM Bukit Moria Tondei satu as field of research, there are several variations of understanding include a wrong understanding. Church people have a diffrent understanding with the bible or theory of experts